1980
DOI: 10.1007/bf00444751
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in bile acid metabolism of infants with the Zellweger (cerebro-hepato-renal) syndrome

Abstract: The bile acid pattern in bile and serum from two infants with the cerebro-hepato-renal syndrome of Zellweger was severely disturbed. An increased concentration particularly of trihydroxycoprostanic acid and also of dihydroxycoprostanic acid could be demonstrated. A generalized mitochondrial defect could explain these increased concentrations. This hypothesis is supported by the abnormal structure of the mitochondria in the liver biopsy of one of our patients. It is possible that the abnormal bile acids contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…The significance of this 1973 find ing was not fully appreciated until it was shown that Zellweger patients had deficient activities of three sets of enzymes that had been localized to the peroxisome. These en zymes control certain steps in the synthesis of plasmalogens [50][51][52][53], oxidation of very long chain fatty acids [54] and certain steps in bile acid synthesis [55][56][57]. The consonance of the morphological (absence of peroxisome) and biochemical (deficient activities of peroxi somal enzymes) led to the realization that the Zellweger syndrome is a model of the effects of a lack of this subcellular organelle.…”
Section: Generalized Peroxisomal Disordersmentioning
confidence: 99%
“…The significance of this 1973 find ing was not fully appreciated until it was shown that Zellweger patients had deficient activities of three sets of enzymes that had been localized to the peroxisome. These en zymes control certain steps in the synthesis of plasmalogens [50][51][52][53], oxidation of very long chain fatty acids [54] and certain steps in bile acid synthesis [55][56][57]. The consonance of the morphological (absence of peroxisome) and biochemical (deficient activities of peroxi somal enzymes) led to the realization that the Zellweger syndrome is a model of the effects of a lack of this subcellular organelle.…”
Section: Generalized Peroxisomal Disordersmentioning
confidence: 99%
“…It is characterized by a reduced number or absence of peroxisomes (3) and regarded as the prototype of peroxisomal deficiency disorders. Multiple peroxisomal biochemical processes are defective, including @-oxidation of very long chain fatty acids (4), phytanic acid oxidation (5,6), pipecolic acid oxidation (7), plasmalogen biosynthesis (8), and bile acid metabolism (9).…”
mentioning
confidence: 99%
“…Zellweger syndrome is also characterized by an increased urinary excretion of trihydroxycoprostanic acid and dihydroxycoprostanic acid (6,9).…”
Section: Patientsmentioning
confidence: 99%